Grassroots engagement and social justice through cooperative extension - Fields, Nia Imani; Shaffer, Timothy J., 1982- (Transformations in higher education., 2022)
"This collection of essays highlights Cooperative Extension's role and responsibility in culturally relevant community education that is rooted in democratic practices and social justice"--